2006
DOI: 10.1111/j.1468-1331.2006.01464.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxcarbazepine and atypical evolution of benign idiopathic focal epilepsy of childhood

Abstract: Patients that have benign epilepsy with centrotemporal spikes (BECTS) may occasionally experience an atypical development in their course when treated with drugs such as carbamazepine. Three patients with electroclinical patterns consistent with BECTS showed seizure exacerbation during oxacarbazepine (OXC) therapy. Two manifested atypical absences, neuropsychological disturbances, and generalized spike-and-wave discharges in their electroencephalograms (EEGs) that became continuous during sleep. The third pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 18 publications
(21 reference statements)
1
20
1
1
Order By: Relevance
“…OXC is already known to exacerbate EEG abnormalities and other recent studies have reported this characteristic [11,27], which was not recorded in our study. The final evaluation regards 24/36 patients, as nine were NR, one showed adverse effect and two exited at the beginning of the study.…”
Section: Discussioncontrasting
confidence: 76%
“…OXC is already known to exacerbate EEG abnormalities and other recent studies have reported this characteristic [11,27], which was not recorded in our study. The final evaluation regards 24/36 patients, as nine were NR, one showed adverse effect and two exited at the beginning of the study.…”
Section: Discussioncontrasting
confidence: 76%
“…In addition, worsening of an ongoing ESES has also been reported (Caraballo et al, 2013). De novo appearance of ESES following the introduction of OXC was observed by Grosso et al (2006) in two out of three children with atypical BECTS. In these two children, OXC provoked an increase in seizure frequency, the appearance of new seizure types, and the extreme activation of EEG epileptic abnormalities during sleep, as in ESES.…”
Section: Discussionmentioning
confidence: 95%
“…However, some reports have shown that OXC may aggravate seizures and worsen the EEG picture in children with idiopathic focal epilepsies of childhood (IFEC), including BECTS (Chapman et al, 2003;Grosso et al, 2006;Vendrame et al, 2007). Neuropsychological deterioration and exaggeration of EEG epileptic discharges during sleep, as seen in ESES, have been described following the introduction of OXC in only two children with atypical IFEC (Grosso et al, 2006). In this report we describe an additional patient in whom treatment with OXC induced ESES.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations